"And the Rabbi Begins the Benediction … ": Declarative Shell Nouns in English. Issue 8 (17th November 2018) - Vergaro, Carla
ABSTRACT: Although in cognitive linguistics it is generally assumed that whether a verb/noun/adjective can or cannot occur in a construction is a matter of compatibility between the meaning of the verb/noun/adjective and the meaning of the construction, in the case of nouns, studies that focus specifically on which substructures (or lack thereof) in the conceptual structure of lexical items are relevant for linking and integration of elements in a construction are missing. In this paper, we focus on nouns and investigate the constructions in which declarative shell nouns, i.e., nouns that report declarative speech acts (e.g., declaration, abrogation, exoneration ) occur. In particular, the patterns in which a set of declarative shell nouns occur are analysed and compared with prevoius results obtained on assertive, and on commissive shell nouns, i.e., nouns that report assertive (e.g., assertion, claim, guess ) and commissive (e.g., promise, threat, bet ) speech acts, with the aim of showing that only specific substructures (or lack thereof) in the conceptual structure of these nouns are relevant for linking and integration, thus explaining the noun behavioural profile, i.e., the constructions they occur with.